ANTIOXIDANT ACTIVITY OF LEAF EXTRACTS OF GLOBIMETULA BRAUNII (ENGLER) VAN TIEGH PARASITIZING ON PILIOSTIGMA THONNINGII AND PARKIA BIGLOBOSA (Jurnal Teknologi (Sciences & Engineering), 2017)
The dried leaves of Globimetula braunii parasitizing on Piliostigma thonningii and Parkia biglobosa were successively extracted using n-hexane, dichloromethane, ethyl acetate and methanol by cold extraction method. All the extracts were evaluated for antioxidant activities using FRAP, ABTS and DPPH assays. The MeOH extract of G. braunii parasitizing on P. thonningii displayed the highest DPPH scavenging activity with SC50 value 2.82 µg/mL while the EtOAc extract of G. braunii parasitizing on P. biglobosa showed highest antioxidant scavenging capacity in the ABTS assay with SC50 value of 138.9 µg/mL. The MeOH extract of G. braunii parasitizing on P. biglobosa showed the highest FRAP equivalent value of 9.68 ± 0.14 mM. These results showed that EtOAc and MeOH are suitable solvents for extraction of active antioxidant agents from the leaves of G. braunii parasitizing on both hosts.